The Hebrew Prophets - NA, NA. author. aut Link
VI, 218 p.
Keywords: The prophets of the Ancient world were mystics whose words have transcended the ages. In this collection, Biblical scholars look at passages from the writings of the period, from Isaiah's portrayal of the suffering Messiah to Daniel's dream of the Ancient of Days pronouncing judgment on the earth, to show their importance for us today.